2013
DOI: 10.1002/glia.22581
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box protein‐1 promotes cerebral edema after traumatic brain injury via activation of toll‐like receptor 4

Abstract: Traumatic brain injury (TBI) is a major cause of mortality and morbidity worldwide. Cerebral edema, a life-threatening medical complication, contributes to elevated intracranial pressure (ICP) and a poor clinical prognosis after TBI. Unfortunately, treatment options to reduce post-traumatic edema remain suboptimal, due in part, to a dearth of viable therapeutic targets. Herein, we tested the hypothesis that cerebral innate immune responses contribute to edema development after TBI. Our results demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
222
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(230 citation statements)
references
References 61 publications
8
222
0
Order By: Relevance
“…The traumatic events leading to the secretion of HMGB1 into the CSF also initiate the secretion of other DAMP into the CSF with successive activation of the innate immune response [25]. Laird et al demonstrated that HMGB1 displayed a supreme neuronal localization within the mouse cerebral cortex and reduce immunoreactivity for HMGB1 was temporally associated with the loss of NeuN within the peri-contusional cortex, suggesting HMGB1 was released by injured neurons into the extracellular space after TBI [27].…”
Section: Mechanisms Of Secretion Of Hmgb1mentioning
confidence: 99%
See 4 more Smart Citations
“…The traumatic events leading to the secretion of HMGB1 into the CSF also initiate the secretion of other DAMP into the CSF with successive activation of the innate immune response [25]. Laird et al demonstrated that HMGB1 displayed a supreme neuronal localization within the mouse cerebral cortex and reduce immunoreactivity for HMGB1 was temporally associated with the loss of NeuN within the peri-contusional cortex, suggesting HMGB1 was released by injured neurons into the extracellular space after TBI [27].…”
Section: Mechanisms Of Secretion Of Hmgb1mentioning
confidence: 99%
“…It has been observed that, over-stimulation of N-methyl-D-aspartate receptors (NMDA-R) by raised extracellular glutamate generate excitotoxicity, an important initiator of neuronal necrosis and edema after TBI [27] [29]. Studies have further demonstrated NMDA-R exist as a tetrameric protein receptor complex made up of two glycine-binding NR1 subunits and two glutamate-binding NR2 subunits that ascertain the biophysical properties [27] [30].…”
Section: Mechanisms Of Secretion Of Hmgb1mentioning
confidence: 99%
See 3 more Smart Citations